Wykorzystanie algorytmów zadań transportowych do optymalizacji dystrybucji energii elektrycznej - Szkutnik, Jerzy (Utilization of the Transport Problem Algorithmus to the Optimization at the Electric Energy Distribution, 2005)
The paper presents the analysis of the electric energy supply cost to the regions. The analysis of this cost is being based on the algorithms of the transport problem. The obtained effects in the supply of the particular distributive companies allow to decrease the electric energy transmission cost on the area of the being analysed energy Group ( which consists of several Distribution companies). Some further researches in this field are being planned; they aim to increase the electric energy distribution affectivity in the Distributive Companies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1078, s. 277-283